Penyuluhan dan Pelatihan TOEFL PBT Sebagai Jembatan Untuk Melanjutkan ke Jenjang Yang Lebih Tinggi di SMA Negeri 2 Pematangsiantar - Damanik, Hasan; Ginting, Agustin Eliasta (UKInstitute, 2022)
The English language proficiency test, in this case the TOEFL, is a language test with an international standard to measure the ability to speak English for speakers whose mother tongue is not English. In Indonesia, there are several conditions that require a person to take the TOEFL test, including to continue to higher education both at home and abroad, fulfill college graduation requirements, find out the level of language skills applying for jobs, and get promoted. In general, there are three types of TOEFL, namely IBT (internet-based test), PBT (paper-based test), and ITP (Institutional Testing Program). Each type of requirement requires a different type of TOEFL test. The output of the solution in this activity is that students gain insight, knowledge and introduction about the importance of TOEFL to be able to continue to a higher level, students can understand the benefits obtained by taking the TOEFL test and getting a TOEFL certificate, students getting tips and tricks in working on questions. TOEFL PBT questions to get the desired TOEFL score, students get TOEFL PBT test experience, students can find out their TOEFL scores by taking the TOEFL PBT test simulation. In this regard, school age is considered the right time to introduce the TOEFL test to students, especially those who will soon graduate and continue their education to a higher level.